Odpowiedzi

2009-05-21T17:46:41+02:00
2009-05-21T17:49:11+02:00
2(x+y)+2=x+6
x+2(x-y)=2+2y

2x+2y+2=x+6
x+2x-2y=2+2y

x+2y=4
x-2y=2

x=4-2y
4-2y-2y=2

x=4-2y
-4y=-2/:(-4)

x=4-2y
y=½

x=4-1
y=½

x=3
y=½
2009-05-21T17:49:42+02:00
2(x+y)+2=x+6
x+2(x-y)=2+2x

2x+2y+2=x+6
x+2x-2y=2+2x

2y+2-6=x-2x
x+2x-2y=2+2x

2y-4=-x /:(-1)
x+2x-2y=2+2x

-2y+4=x
x+2x-2y=2+2x

-2y+4=x
x=2+2y

-2y+4=2+2y

-2y-2y=2-4

-4y=-2 /:(-4)

y=1/2

x=2+2y --> x=2+2*1/2=3
2009-05-21T17:50:20+02:00
2x + 2y + 2 = x + 6
2x + 2y - x = 6 -2
x + 2y = 4
x = 4 - 2y

x + 2x - 2y = 2 + 2x
x + 2x - 2y - 2x = 2
x - 2y = 2 => pod x podstawiamy 4 - 2y
(4 - 2y) - 2y = 2
4 - 2y -2y = 2
-4y = 2-4
-4y = -2/ (-4)
y = 1/2

x = 4 - 2y => po y podstawiamy 1/2
x = 4 - 2* 1/2
x = 4 - 1
x = 3

y = 1/2, a x = 3
2009-05-21T17:51:34+02:00
1.2(x +y)+2=x+6
2x+2y+2=x+6
2x-x+2y=2+6
x-2y=8


2.x+2(x-y)=2+2x
x+2x-2y=2+2x
x+2x-2x=2
x=2
2009-05-21T17:53:01+02:00
1.2(x +y)+2=x+6
2x+2y+2=x+6
2x-x+2y=2+6
x-2y=8


2.x+2(x-y)=2+2x
x+2x-2y=2+2x
x+2x-2x=2
x=2